1992
DOI: 10.1007/bf01849748
|View full text |Cite
|
Sign up to set email alerts
|

Three years' experience with levonorgestrel-releasing intrauterine device and Norplant-2 implants: a randomized comparative study

Abstract: A randomized comparative study of levonorgestrel-releasing intrauterine device (LNG-IUD) and Norplant-2 implants was carried out in 200 women for 36 months. Three thousand one hundred woman-months of use were observed with each device. Only one pregnancy occurred in users of LNG-IUD at the 12th month of use. The change in bleeding pattern was the most frequent reason for discontinuation. The discontinuation rate for irregular bleeding with Norplant-2 was 17.3 and 26.8 at 24 and 36 months, respectively, as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…Three studies 20,34,35 compared the levonorgestrel‐20 intrauterine system with intrauterine devices > 250 mm 3 and three 15,27,34 compared the levonorgestrel‐20 intrauterine system with intrauterine devices > 250 mm 3 . The two remaining comparisons were the levonorgestrel‐20 intrauterine system versus Norplant rods 31 and the levonorgestrel‐20 intrauterine system versus the levonorgestrel‐intracervical device 12 . Five studies reported that all participants had proven fertility 12,20,27,31,34 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies 20,34,35 compared the levonorgestrel‐20 intrauterine system with intrauterine devices > 250 mm 3 and three 15,27,34 compared the levonorgestrel‐20 intrauterine system with intrauterine devices > 250 mm 3 . The two remaining comparisons were the levonorgestrel‐20 intrauterine system versus Norplant rods 31 and the levonorgestrel‐20 intrauterine system versus the levonorgestrel‐intracervical device 12 . Five studies reported that all participants had proven fertility 12,20,27,31,34 .…”
Section: Resultsmentioning
confidence: 99%
“…The two remaining comparisons were the levonorgestrel‐20 intrauterine system versus Norplant rods 31 and the levonorgestrel‐20 intrauterine system versus the levonorgestrel‐intracervical device 12 . Five studies reported that all participants had proven fertility 12,20,27,31,34 . The study by Sivin et al 20 was the longest, with seven years follow up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some early studies (including the Finland/Brazil Study) included the LNG-IUDs that released 30/zg of levonorgestrel daily (the LNG-IUD-30) for comparison. A few other clinical trials with smaller study populations have been reported from China comparing the IUD that releases 2/zg of levonorgestrel daily (LNG-IUD-02) with IUDs made in China [17,18], or the LNG-IUD-20 with Norplant implants [19,20]. Other aspects of the LNG-IUD-20, like return of fertility [15,[21][22][23], use by postpartum and/or lactating women [24,25], or using the LNG-IUD-20 as a treatment for menorrhagia or dysmenorrhea [13,[26][27][28][29], have been reported sporadically, mostly by Scandinavian or British investigators.…”
Section: Methodsmentioning
confidence: 99%